(untitled) (Bangladesh Journal of Agricultural Research, 2010)
The present study was undertaken to investigate the effect of different combinations of NAA, IBA, and BAP on in vitro organogenesis of Anthurium andreanum cv. "Nitta" at the DEBTEC (Development of Biotechnology & Environmental Conservation Centre) Laboratory, Dhaka. Organogenesis from leaf mid rib to shoot initiation required 9.00 days and the best survivality was 80.00% percent at 30 DAI (Day after initiation) with the combination of 1 mg/L NAA and 1 mg/L BAP in MS media. Among the 20 hormone supplements, MS media containing 1 mg/L NAA and 1 mg/L BAP showed the highest shoot formation (68.30%), number of shoots/explant (3.37) and the longest shoot (4.65 cm) at 60 DAI. MS media without any hormone (control) showed the poorest performance in regeneration of shoots. On the other hand, MS media containing 1 mg/L IBA + 1 mg/L BAP showed the best performance in rooting of shoots (83.85%), highest number of roots (4.29/plantlet), root elongation (5.50 cm) were recorded at 60 DAI. Keywords: In vitro regeneration; Anthurium andreanum. DOI: 10.3329/bjar.v35i2.5884 Bangladesh J. Agril. Res. 35(2) : 217-226, June 2010